Selected ceramics from Novae – 1983 campaign - Dyczek, Piotr (Balcanica Posnaniensia. Acta et studia, 1990)
The article discusses selected ceramic materials discovered during the excavation campaign at Novae in 1983. The research problem concerns the identification of the origin, function, and chronology of the ceramics in the context of settlement transformations after the decline of the military function of the fortress. The aim of the work is to analyze the ceramic material and its interpretation in light of the stratigraphy of trench DW 3. The author applies archaeological methods, including analysis of layers, technology of vessel production, and typological comparisons. The most important results indicate that the ceramic material mainly dates from the turn of the 3rd and 4th centuries AD, which is also confirmed by coin finds (including Aurelian, Probus, and Diocletian). Amphora fragments dominate (about two-thirds of the material), produced mainly locally in centers such as Butovo and Hotnica, although some vessels were imported from Dacia, the Black Sea region, and even the Bosporus. Technological analysis (type of clay, inclusions, surface treatment) allowed the distinction of different production groups. The conclusion is the confirmation of intensive trade contacts of Novae and the continuity of civilian settlement after the decline of its military function.